Strategic entrepreneurship and SMEs performance: The mediation effect of competitive advantage - Endi Sarwoko; Iva Nurdiana Nurfarida; Aria Ganna Henryanto (Jurnal Ekonomi Modernisasi, 2025)
The aim of the study is to examine the effect of entrepreneurial leadership and entrepreneurial mindset on competitive advantage and business performance using a strategic entrepreneurship model in the context of SMEs. This study uses a survey method, data were collected using a questionnaire from 258 SME owner/managers in Indonesia. The proportional random sampling technique was used to select the sample, and PLS-SEM was used for data analysis. The study reveals that entrepreneurial leadership and entrepreneurial mindset had a positive effect on SME performance. The mediating role of competitive advantage was also explained in the relationship between entrepreneurial leadership, entrepreneurial mindset and SME performance. According to the dynamic capability theory, SME possessed the ability to change through strategic entrepreneurial choices. This research was conducted in one country and the results were difficult to generalize. Power distance or decision-making authority was not considered in leadership. Therefore, other results are needed from countries with different cultural contexts to expand the generalization of the research. This research offers novel insights of the importance of strategic entrepreneurship to enhance competitive advantage and business performance in the context of SMEs.